PENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE INKUIRI MATA PELAJARAN PKN KELAS IV SD NEGERI 164525 KOTATEBING TINGGI - Nurmala Simanjuntak (PGSD Universitas Negeri Medan, 2018)
This purposes of this research is to improve learning result on PKn subject through Inquiry method. This classroom action research conducted by 3 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SD N 164525 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of PKn subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (51,51%), the first cycle (57,57%), cycle II (81,81%), the third cycle (90,90 %) and complete learn the clasical equal to 90,90 %.Keywords : Inquiry, learning result, PKN